2019
DOI: 10.51985/jbumdc2019010
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing The Choice Of Ophthalmology As A Career Amongst Students Of Dow University Of Health Sciences, Karachi

Abstract: Objective: To determine the factors influencing the choice of Ophthalmology as a career amongst Dow University of Health Sciences, Karachi. Study design and Setting: A descriptive cross sectional study was conducted on fourth and final year students of Dow Medical College, DUHS, Karachi through non-probability consecutive sampling technique. Methodology: Before conducting the study, permission from the Principal of Dow Medical College, Dow University of Health Sciences was taken. Overall 244 students were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…2 Another study by Hamid S et al, in 2019 conducted on the fourth and final year medical students, and house officers showed that only 3.8% of the participants were interested in Ophthalmology as a future subject of speciality, with a male to female ratio being 1:3, which is alarming as well 3 . The main factors influencing medical students not to choose Ophthalmology include, fewer chances of residency, prolonged duration of residency, and limited opportunities in the private sector 4 . Besides this, students often perceived Ophthalmology as a 'dry subject'.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Another study by Hamid S et al, in 2019 conducted on the fourth and final year medical students, and house officers showed that only 3.8% of the participants were interested in Ophthalmology as a future subject of speciality, with a male to female ratio being 1:3, which is alarming as well 3 . The main factors influencing medical students not to choose Ophthalmology include, fewer chances of residency, prolonged duration of residency, and limited opportunities in the private sector 4 . Besides this, students often perceived Ophthalmology as a 'dry subject'.…”
mentioning
confidence: 99%
“…Though there are many benefits of choosing the field as a speciality, some being high income, less working hours and no duties in the night 4 . Almost all cases in Ophthalmology are treated in daycare settings and the surgeries are also mainly elective procedures as there are fewer emergency calls.…”
mentioning
confidence: 99%